Pengaruh Mutasi, Shift, Komitmen Organisasi dan Training Terhadap Kinerja Karyawan pada PT.Otsuka Indonesia (Studi Kasus Karyawan Inspeksi Packing Softbag PT. Otsuka Indonesia) - muh mahfut mashuri; nuzunul Rachma; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The purpose of this research is to determine and analyze 1) mutations, shifts, organizational commitment and training have a simultaneous effect on employee performance 2) mutations affect employee performance 3) shift affects employee performance 4) organizational commitment affects employee performance 5) training has an effect on the effect on employee performance. This research is an explanatory research, with the population being the research object is the employees of the inspection section of the softbag packing of PT. Otsuka Indonesia, as many as 83 people. The data analysis method used is multiple linear regression analysis using the F test and t test. Based on the results of research and discussion, it can be concluded that mutations, shifts, organizational commitment and training have a significant effect simultaneously on employee performance. Mutation has a partially significant effect on employee performance, shift has a partially significant effect on employee performance, organizational commitment has a partially significant effect on employee performance and training has a partially significant effect on employee performanceKeywords: Movements, Shifts, Organizational Commitment, Training and Employee Performance